Konstitusionalitas Perbuatan Tidak Menyenangkan Sebagai Tindak Pidana Ujaran Kebencian: Analisis Surat Edaran Kapolri Nomor: Se/6/X/2015 - Peter Jeremiah Setiawan; Xavier Nugraha; Vincentius Sutanto; Marchethy Riwani Diaz (Universitas Medan Area, 2021)
This article aims to analyze the position of unpleasant acts as a form of hate speech (haatzaai articlesen), which in fact the concept of unpleasant acts has been eliminated by the Constitutional Court Decision Number 1 / PUU-XI / 2013, The problem is focused on the constitutionality of wrongdoing. fun as a form of hate speech (haatzaai articlesen). In order to approach this problem, a theoretical reference from the element theory of crime and the theory of constitutionality of norms is used. This research is a normative legal research, so that the data is collected through literature studies, both on primary, secondary and tertiary legal materials. This research was analyzed qualitatively. This study concludes that: (1) With the Constitutional Court Decision Number 1 / PUU-XI / 2013 which is legally binding, then every legal norm in statutory regulations made after the Constitutional Court Decision must comply with the provisions with does not bring back the existence of the phrase